Day resting site use and fidelity of alpine otters (Lutra lutra) on southeast Austria - Freire, Susana Isabel Marques, 1988- (2011)
Tese de mestrado. Biologia (Biologia da Conservação). Universidade de Lisboa, Faculdade de Ciências, 2011 The availability of resting sites is known to influence the distribution and density of animals and they are key resources to nocturnal mammals that need to spend daylight in safe refuges. This is the reason why these structures have to be taken in account in the efforts of mammal species conservation. Aside from being simply a place to rest, these structures also provide natural protection against predators and thermal isolation in harsh environments. In the 1960’s Eurasian otters (Lutra lutra) crashed in many parts of its European distribution, this being the case of Austria. With the species recolonization, favored by an interconnection with the Czech and the Hungarian populations, a need emerged for a better understanding on how animals are using such resources in the Alpine landscape as the species is still considered endangered. The main goals of this study were to evaluate (assess) if: (1) there is a structural pattern of daytime resting site according to gender and age; (2) human disturbance affects the choice of resting site type; (3) snow cover has any influence on the type of resting site used; (4) rest-site choice can be predicted based on environmental variables and (5) there is a geographic pattern in resting site choice. Four otters (two adult females, one adult male and one juvenile female) were captured and radio-tagged to locate resting structures which were characterized according to a set of physical and environmental parameters. Daily climate data was obtained from local weather stations. In spite of sampling size constrains results revealed that underground structures were used more often than surface lairs and suggest a different use of resting site type between females and breeding females. No relation was found between rest-site type and human density. Snow cover influence could not be asserted due to environmental conditions during the sampling period, but temperature, vegetation ...